Effects of water quality changes on the recreation benefits of swimming in Finland: Combined travel cost and contingent behavior model - Lankia, Tuija; Neuvonen, Marjo; Pouta, Eija (Elsevier, 2017)
Finland is a highly coastal country with a large archipelago area and numerous lakes. Consequently, these provide an essential environment for water-based outdoor recreation activities. To improve the information base for evaluating the welfare effects of policy instruments addressing water quality, such as the EU Water Framework Directive, this study examined the effects of changes in water quality on the recreation benefits, focusing on swimming trips in Finland. National recreation inventory data were used to provide information on welfare changes at the national level. The combined travel cost and contingent behavior approach revealed that the recreation value of a swimming trip in the current state was approximately 16 euros. The approach allowed assessment of the welfare effects of water quality changes beyond the observed levels, showing that a hypothetical decrease in water quality to a level at which the water visibility would be less than 1 m and abundant slime would exist decreased the value to 9 euros. Water quality improvement to a level at which the perceived water visibility would be over 2 m and no slime would exist increased the value per trip to 22 euros. In total, the overall annual value of all visits made for swimming in the case of water quality improvement increased the recreation benefits by 53–80%, while a deterioration in quality decreased the benefits by approximately 80%.
Keywords: Water; quality; valuation; recreation; vedenlaatu; virkistyskäyttö